2009
DOI: 10.1111/j.1440-1746.2009.05996.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of adipose restriction and metabolic factors in progression of steatosis to steatohepatitis in obese, diabetic mice

Abstract: In mice genetically predisposed to obesity and diabetes, HF feeding leads to restriction of adipose tissue for accommodation of excess energy, causing lipid partitioning into liver, and transformation of simple steatosis to fibrosing steatohepatitis. The way in which HF feeding 'saturates' adipose stores, decreases serum adiponectin and causes hepatic inflammation in steatohepatitis may provide clues to pathogenesis of NASH in metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 33 publications
12
90
0
Order By: Relevance
“…As reported [19,22], foz/foz mice were heavier than Wt at 3 and 6 mths ( Figure 1A), with increased adiposity (peri-epi-didymal white adipose tissue (WAT) mass; Figure 1B) and hepatomegaly ( Figure 1C Figure 2A). As shown in Figure 2B, histological examination of these tumors showed features described as the steatohepatitic variant of HCC, with large-droplet steatosis and mild inflammatory cell infiltration [23].…”
Section: Den-induced Hepatocarcinogenesis Is Accelerated In Foz/ Foz supporting
confidence: 71%
See 1 more Smart Citation
“…As reported [19,22], foz/foz mice were heavier than Wt at 3 and 6 mths ( Figure 1A), with increased adiposity (peri-epi-didymal white adipose tissue (WAT) mass; Figure 1B) and hepatomegaly ( Figure 1C Figure 2A). As shown in Figure 2B, histological examination of these tumors showed features described as the steatohepatitic variant of HCC, with large-droplet steatosis and mild inflammatory cell infiltration [23].…”
Section: Den-induced Hepatocarcinogenesis Is Accelerated In Foz/ Foz supporting
confidence: 71%
“…Gene and protein expression were assayed using semi-quantitative real time PCR and immunoblotting, respectively as previously reported [22]. Primer sequences and antibody conditions will be supplied upon request.…”
Section: Analysis Of Hepatic Genes and Proteinsmentioning
confidence: 99%
“…Therefore, the increased fat intake could be a contributing factor for central adiposity and hepatic steatosis. It has also been shown that a high-fat diet in genetically predisposed obese and diabetic mice caused earlier onset of steatohepatitis and rapid transformation of simple steatosis to fibrosing steatohepatitis (Larter et al, 2009). This observation suggests that diet therapy, particularly control of fat content in meals, should be recommended in NAFLD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patients with NAFLD consuming a diet high in carbohydrates have greater odds of hepatic inflammation (Kang et al, 2006) suggesting a link between diet and liver injury. It has also been reported that there is an early development of steatohepatitis in obese, hypercholesterolemic, diabetic foz/foz mice fed on high-fat diet for 12 months (Larter et al, 2009). However, the inter-relations of NAFLD, MS, dietary composition and physical activity have been sparsely studied in asymptomatic healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…3 Dietary deficiency of methionine and choline also contribute to development of steatosis and mild fibrosis, without obesity and insulin resistance. 3 In this regard, Larter et al 32 recently reported that foz/foz mice, carrying truncating mutation in Alms1, demonstrated both obesity and NASH-like liver histologic features during long-term feeding of an HFD. This study has established MC4R-KO mice fed the HFD for a relatively short time as a novel rodent model of NASH with obesity, insulin resistance, and excessive accumulation of lipids and enhanced fibrosis in the liver.…”
Section: Discussionmentioning
confidence: 99%